To simplify the given expression, we can start by using the distributive law.
Step 1: Distribute the negation (¬) in the first part of the expression:
¬(d∨((¬b∧c)∨(b∧¬c)))
Step 2: Distribute the negation (¬) further inside the first part:
¬(d∨(¬b∧c)) ∧ ¬(d∨(b∧¬c))
Step 3: Apply De Morgan's laws and distribute the ∧ (logical AND) inside the first part:
(¬d∧(¬¬b∨¬c)) ∧ (¬d∧(¬b∨¬¬c))
Step 4: Simplify the double negations (¬¬):
(¬d∧(b∨¬c)) ∧ (¬d∧(¬b∨c))
Step 5: Apply the distributive law again to the second part of the expression:
((¬d∧b)∨(¬d∧¬c)) ∧ ((¬d∧¬b)∨(¬d∧c))
Step 6: Simplify the expressions with ∧ (logical AND):
((-d∧b)∨(-d∧¬c)) ∧ ((-d∧¬b)∨(-d∧c))
Step 7: Apply the distributive law once more:
(-d∧(b∨¬c))∨(-d∧(¬b∨c))
Step 8: Simplify the expressions with ∨ (logical OR):
(-d∧(b∨¬c))∨(-d∧(¬b∨c))
Step 9: Apply the distributive law to the ∨ (logical OR) outside the parentheses:
(-d∧b) ∨ ¬c ∨ (-d∧¬b) ∨ c
Step 10: Simplify the expressions with ∨ (logical OR) and ∧ (logical AND):
((-d∧b) ∨ (-d∧¬b)) ∨ ¬c ∨ c
Step 11: Simplify the expressions with ∧ (logical AND):
-d ∨ ¬c ∨ c
Step 12: Simplify the expressions with ∨ (logical OR):
-d ∨ 1
Answer:
-d ∨ 1